Comparative Efficacy of Transfemoral Prosthetic Interfaces: Analysis of Gait and Perceived Disability. Issue 3 (July 2017) - Klenow, Tyler D.; Kahle, Jason T.; Fedel, Frank J.; Ropp, Jeffrey; Highsmith, M. Jason
ABSTRACT: Introduction: The High-Fidelity (HiFi) interface is an emerging transfemoral interface technology. However, no comparison of this interface to traditional transfemoral interface designs is currently available. The purpose of this study is to measure the effects of the HiFi system on gait and perceived disability compared with a traditional socket design in a subject with transfemoral amputation. Methods: The subject was first tested with a traditional ischial containment socket, then fit with the HiFi system, and tested again after a 30-day accommodation period. Three-dimensional motion analysis was performed using an 8-camera Vicon Motion Capture system. The Oswestry Low Back Pain Disability Questionnaire v2.0 and Western Ontario and McMaster University Osteoarthritis index were administered at initial and secondary testing to evaluate perceived disability. A one-way analysis of variance and Fischer's least significant difference were used to determine statistical difference between conditions. The level of significance for all tests was set at P ⩽ 0.05. Results: Notable results included an increase in self-selected gait velocity, prosthetic hip adduction, and hip extension. Reductions in lateral center of mass deviation during gait and in perceived disability was also shown with use of the HiFi condition. Discussion: This study analyzed the effects of the HiFi Interface System on biomechanical parameters of gait and perceived disability compared with a baseline IRC condition in this elderly subject with history of TF amputation. Several improvements and markers of increased stability with use of the HiFi were noted. Perceived disability was also greatly improved comparatively. Conclusions: The HiFi Interface System presented some biomechanical advantages to traditional IRC socket designs in this case, which may allow for increased stability in patients utilizing a TF prosthesis. Further research with larger samples is warranted.